2022
DOI: 10.1371/journal.pone.0275527
|View full text |Cite
|
Sign up to set email alerts
|

Intake of nutrients (polyunsaturated fatty acids, tocols, and carotenes) and storage efficiency in different slow-growing chickens genotypes reared in extensive systems

Abstract: An extensive rearing system (ERS) for poultry requires an outdoor run, which enhances the foraging activity of chickens. Slow-growing (SG) strains are more adapted to ERS than fast-growing (FG); and generally, have higher levels of bioactive compounds in their meat. The aim of this paper was to assess the storage efficiency of n-3 and n-6 polyunsaturated fatty acids (PUFA), tocols and carotenes in the meat of seven commercial SG genotypes (SG1-7). One hundred SG chicks/strain of both sexes were included and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Following similar trends, uric acid concentration, which acts as an antioxidant 35,36 , also decreased with range use in the strain S757N. Our observations are quite consistent with previous results that showed that locomotor activity (which is likely higher in HR chickens than in LR chickens) of Ross 308 broilers and other slow-growing strains are correlated to higher oxidative indicators and lower antioxidant concentration in the blood 11,18,37 . Therefore, range use seems to induce an imbalanced redox status in the JA757 strain, characterized by the highest growth rate among the studied strains.…”
Section: Broilers' Parameters Divergence With Range Usesupporting
confidence: 91%
See 4 more Smart Citations
“…Following similar trends, uric acid concentration, which acts as an antioxidant 35,36 , also decreased with range use in the strain S757N. Our observations are quite consistent with previous results that showed that locomotor activity (which is likely higher in HR chickens than in LR chickens) of Ross 308 broilers and other slow-growing strains are correlated to higher oxidative indicators and lower antioxidant concentration in the blood 11,18,37 . Therefore, range use seems to induce an imbalanced redox status in the JA757 strain, characterized by the highest growth rate among the studied strains.…”
Section: Broilers' Parameters Divergence With Range Usesupporting
confidence: 91%
“…Additionally, breast meat of HR was yellower than that of LR in both JA757 and dual-purpose strains. Increased yellowness has been reported in several other studies 10,27,28 and could be caused by the intake of fresh plants (e.g., grass or clover) containing carotenoids 11,29 . We can hypothesize that JA757 and dual-purpose highrangers dedicated a higher percentage of their time to foraging activities, and/or their metabolism is able to assimilate more pigments than other strains from the ingested plants, leading to a higher enrichment of their muscles in carotenoids.…”
Section: Range Use and Welfare Indicators At Slaughtermentioning
confidence: 58%
See 3 more Smart Citations